Study of the mechanical behavior of starch-cotton fiber waste composite sheets - GBEGBO, Eric; DOKO, KOUANDETÉ VALERY; TOUKOUROU, CHAKIROU A. (My University, 2023)
In Africa, the cotton industry is one of the most important agricultural sectors. In Benin, a record 730,000 tonnes will be produced in 2020-2021, making the country the leading producer of the white gold in Africa. Although essential to the economy, fourteen types of residue from cotton processing remain unexploited. This waste is generally burnt by producers, which contributes to environmental pollution through the emission of greenhouse gases. To overcome this problem, we focused our work on recycling cotton fiber waste into a cotton fiber-starch composite material for use as false ceiling panels in the building industry, in place of the plywood generally used. To achieve this, we manufactured sheets from our composite material to determine mechanical properties such as modulus of elasticity and flexural modulus of rupture in accordance with NF EN 310. Three-point bending loading-unloading cycles were performed. The plates manufactured have dimensions of 300x300x100mm3. The plates are manufactured with «starch/water» and «starch/cotton fiber» mass ratios respectfully equal to 0.25 and 1. We obtained a modulus of elasticity equal to 2830 MPa and a modulus of rupture equal to 11.53 MPa.
Keywords: Composite material; cotton fiber; starch; numerical simulation.